Presence of Diverse Sugarcane Bacilliform Viruses Infecting Sugarcane in China Revealed by Pairwise Sequence Comparisons and Phylogenetic Analysis - Ahmad, Kashif (Plant Pathol J, 2019)
Sugarcane bacilliform viruses (SCBV), which belong to the genus Badnavirus, family Caulimoviridae, are an important DNA virus complex that infects sugarcane. To explore the genetic diversity of the sugarcane-infecting badnavirus complex in China, we tested 392 sugarcane leaf samples collected from Fujian, Yunnan, and Hainan provinces for the occurrence of SCBV by polymerase chain reaction (PCR) assays using published primers SCBV-F and SCBV-R that target the reverse transcriptase/ribonuclease H (RT/RNase H) regions of the viral genome. A total of 111 PCR-amplified fragments (726 bp) from 63 SCBV-positive samples were cloned and sequenced. A neighbor-joining phylogenetic tree was constructed based on the SCBV sequences from this study and 34 published sequences representing 18 different phylogroups or genotypes (SCBV-A to -R). All SCBV-tested isolates could be classified into 20 SCBV phylogenetic groups from SCBV-A to -T. Of nine SCBV phylogroups reported in this study, two novel phylogroups, SCBV-S and SCBV-T, that share 90.0–93.2% sequence identity and show 0.07–0.11 genetic distance with each other in the RT/ RNase H region, are proposed. SCBV-S had 57.6–92.2% sequence identity and 0.09–0.66 genetic distance, while SCBV-T had 58.4–90.0% sequence identity and 0.11–0.63 genetic distance compared with the published SCBV phylogroups. Additionally, two other Badnavirus species, Sugarcane bacilliform MO virus (SCBMOV) and Sugarcane bacilliform IM virus (SCBIMV), which originally clustered in phylogenetic groups SCBV-E and SCBV-F, respectively, are first reported in China. Our findings will help to understand the level of genetic heterogeneity present in the complex of Badnavirus species that infect sugarcane.